PROLONGED ESTRUS IN A BITCH - DIAGNOSIS AND MANAGEMENT - SOOD, PANKAJ; VASISHTA, N K; SINGH, MADHUMEET (The Indian Journal of Animal Reproduction, 2023)
A Labrador bitch was presented with a history of sanguinous genital discharge for 30 days. The bitch was diagnosed to be in prolonged estrus that was successfully treated with multiple injections of hCG.